Peningkatan Hasil Belajar Siswa Menggunakan Model Contextual Teaching and Learning pada Materi Keragaman Budaya Indonesia di Kelas IV UPTD SD Negeri 1 Peusangan Selatan - Merdu Mahbengi; Yulia Santi; Maisura (Indo Publishing, 2025)
This study aims to determine the improvement of student learning outcomes, teacher and student activities, and student responses to the use of the Contextual Teaching and Learning (CTL) learning model on the material of Indonesian cultural diversity in grade IV of UPTD SD Negeri 1 Peusangan Selatan. This study uses a qualitative approach with the type of Classroom Action Research (CAR) which is implemented in two cycles. The subjects of the study were 22 grade IV students. Data collection techniques include learning outcome tests, observation sheets, and questionnaires. Data were analyzed using learning completeness analysis and the percentage of observer answers. The results of the study showed an increase in student learning outcomes, namely in cycle I by 63% increasing to 86.36% in cycle II. Teacher activity also increased from 72.94% in cycle I to 91.77% in cycle II. Similarly, student activity increased from 67.94% in cycle I to 88.83% in cycle II. This increase indicates that the application of the CTL model is able to create a more active and effective learning process. Student responses to learning using the CTL model were very positive, with 82.52% responding with